Behaviour and Satisfaction Effects on User Loyalty within e-Procurement of National Oil Firms - Purbanuara Parlindungan; Lim Sanny; Sita Aniisah Sholihah; Nofrisel Nofrisel; Zaroni Zaroni (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to analyze the effects of Application Ease of Use, Digital Service Quality, and Digital Information Quality on User Behavior, User Satisfaction, and User Loyalty in National Upstream Oil and Gas Companies. It also examines the mediating roles of User Behavior and User Satisfaction in influencing loyalty. Research Methodology: A quantitative approach was used with the SmartPLS 4 analysis tool to analyze the data. Data were collected from 296 respondents across 15 upstream oil and gas companies in Indonesia, selected through purposive sampling based on Slovin’s formula. The analysis employed the Structural Equation Modeling (SEM-PLS) technique to test the direct and indirect effects of the study variables. Results: The findings revealed that Ease of Use and Digital Service Quality significantly influenced both user behavior and satisfaction. Digital Information Quality does not significantly affect User Behavior but has a strong impact on User Satisfaction. Furthermore, User Behavior and User Satisfaction significantly enhance User Loyalty, confirming their mediating roles. Conclusions: Ease of Use and Service Quality are critical determinants of user engagement and loyalty, whereas Digital Information Quality primarily strengthens satisfaction. Limitations: This study focused only on upstream oil and gas companies in Indonesia and used cross-sectional self-reported data, which may limit causal interpretation. Contribution: This study enriches digital loyalty theory by highlighting how behavioral and satisfaction factors mediate the impact of digital quality dimensions on user loyalty in industrial digital systems.